PENGARUH KOMPLEKSITAS AUDIT DAN RISIKO KEUANGAN TERHADAP AUDIT FEE PERUSAHAAN PERBANKAN DI BEI 2019 – 2020 - Betsyeba Anggriani; Mila Susanti (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The financial performance of bank companies listed on the exchange can not be separated from public confidence with financial statements that are always published by the company every year. Therefore, the purpose of this study is to find out the complexity of audt and financial risks to audit fees both partially and simultaneously. The study used quantitative methods with causal associatives. Population data as much as 43 data, but there are only 34 data that can be processed and analyzed. Data obtained from the financial statements of banking sector companies listed on the IDX 2019-2020. The results of this study showed that there was no significant effect on the complexity of the audit on the audit fee partially. In the next independent variable, there is a significant influence on financial risk on audit fees. And recent results show there is a significant influence on audit complexity and financial risk to audit fees simultaneously.